Respuesta :

Answer:

[tex]\left( x-2\right)^{2} +\left( y-6\right)^{2} =12[/tex]

Step-by-step explanation:

Formula ………………………………………………………………………

The equation of a circle with center (a , b) and radius r is :

[tex]\left( x-a\right)^{2} +\left( y-b\right)^{2} =r^{2}[/tex]

===================

Now ,let’s apply what we have learnt:

The equation of the circle with center (a , b) = (2 , 6) and radius r = 2√3 is :

[tex]\left( x-2\right)^{2} +\left( y-6\right)^{2} =\left( 2\sqrt{3} \right)^{2}[/tex]

[tex]\Longleftrightarrow \left( x-2\right)^{2} +\left( y-6\right)^{2} =12[/tex]

[tex]\text{Note :} \left( 2\sqrt{3} \right)^{2} =2^{2}\times \sqrt{3}^{2} =4\times3=12[/tex]

ACCESS MORE